On the style of the Bachkovo Ossuary frescoes - Oretskaia Irina (Zograf, 2018)
The article attempts to give a thorough description of the style of the Bachkovo Ossuary frescoes and to draw analogies for their artistic manner and single figures. They appear to reveal the closest similarity with some miniatures found in Greek manuscripts of the late eleventh century. Several common artistic methods were used in the Bachkovo frescoes and in the monumental painting of that time as well. They also include some motifs, which were well-known to artists of the second half of the twelfth century. The style of the Ossuary frescoes has been correctly described as classical in most of the pertinent studies. All the components of this style took shape already in the late eleventh century; however, it is not impossible that the frescoes were created later, in the twelfth century.